The Impact of Back-translation Instruction with Collaborative Activities on Iranian English Students’ Translation Achievement - Mohammadi, Hesam; Beiki, Maryam; Keyvanfar, Arshya (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The present quasi-experimental study with a non-equivalent control group pretest-posttest design investigated the impact of back-translation teaching with collaborative activities on Iranian English translation students’ translation achievement. To this end, 30Iranian EFL translation students studying at Islamic Azad University North Tehran Branch were nominated based on convenience sampling. The Oxford Placement Test (OPT) and a translation pretest were directed to inspect the contributors’ homogeneity prior to the treatment. The groups were assigned to the Collaborative Back-translation Group (CBTG n=15) and Back-translation Group (BTG n=15). During 16 sessions, CBTG experienced back-translation with collaborative activities as a treatment, whereas the BTG experienced only back-translation every session. After the treatment stage, the participants were given a translation posttest. The study also examined the participants’ attitudes toward collaborative activities implementation via semi-structured interviews and tried to assess some students’ perceptions towards collaborative activities and the instructional practices in the university context. The qualitative analysis revealed that most learners preferred collaborative tasks in their classrooms. The quantitative analysis showed that the CBTG outdone the BTG in translation ability. The result of the present research had some implications for the teachers and students in translation pedagogy. As for the theoretical aspect, this study can provide some hints for researchers interested in developing a comprehensive model for the L2 translation process. Considering the practical implications, all the instructors could employ a set of collaborative activities in their translation classes. Collaborative activities create translating opportunities where students exchange meaning, suggest feedback, and offer enhanced output for revealing the meaning.